VARIABILITY OF BIOCHEMICAL PARAMETERS OF AMARANTH PLANTS DURING CULTIVATION TO OBTAIN THE NATURAL FOOD COLORANT WITH A HIGH CONTENT OF BIOLOGICALLY ACTIVE SUBSTANCES - M. S. Gins; V. K. Gins; A. A. Baikov; M. M. Tareeva; S. Yu. Platonova; M. K. Torres; A. F. Pelii (Овощи России, 2018)
Amaranth leaves can be used in salads, soups, sauces enriching them with biologically active substances (in particular, ascorbic acid and phenolic compounds), as well as giving them an original taste and color. Plants were grown on the experimental field of VNIISSOK in the Moscow region. The experiment was laid on sod-podzolic soil. For the period of 2013-2016 years, biochemical parameters were investigated: total content of water-soluble antioxidants, ascorbic acid content, dry matter content, amarantine content in three amaranth varieties (Valentina, Don Pedro and Fakel) and two green leaf varieties (Pamyati Kovasa and Eku 17020) of FSBSI FSVC (formerly VNIISSOK) and INIAP selection and a correlation analysis was performed, which showed a relationship between the relative concentration of amarantine in the leaves and other biochemical parameters at different stages of plant development. The maximum accumulators of antioxidants according to the TAC parameter were the Valentina and Don Pedro varieties - up to 2.9 mg gallic acid equivalents/g. The situation was similar in terms of the content of the reduced form of ascorbic acid. So also the Valentina and Don Pedro varieties were leading with values of about 140 mg%. A positive correlation between the content of ascorbic acid and the sum of hydrophilic antioxidants was confirmed. Pamyati Kovasa and Eku 17020 varieties can be recommended as a source of green mass of leaves with a high content of ascorbic acid, red colored varieties Don Pedro, Valentina, Fakel – for obtaining red dye enriched with antioxidants.